PENGARUH TINGKAT PENDIDIKAN, UPAH MINIMUM,DAN PDRB TERHADAP PENYERAPAN TENAGA KERJA DIKABUPATEN/KOTA PROVINSI JAWA BARAT - Attifah Meita Rahmah (2022)
West Java Province is an economic center that has a large number of productive age population in Indonesia who will face a period of demographic bonus. The high level of unemployment in the area is an employment problem which indicates that labor absorption is not yet optimal with several factors that can influence it. This study uses panel data with the data used are 6 regencies/cities in West Java Province which are included in areas with a large number of works absorbed in the 2015 - 2020 period. The random effect model is the best model chosen. This study can show that the level of education and the minimum wage have an effect on employment in the Regency/Coty of West Java Province, but GDRP has no effect.